Dielectric ceramics and ceramic capacitors using the same

The dielectric ceramic, with a controlled island-like structure and specific composition, successfully achieves both high dielectric constant and low dielectric loss tangent, addressing the challenges faced by existing ceramic materials in ceramic capacitors.

JP7655447B2Active Publication Date: 2025-04-02MURATA MFG CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024522403
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-02-28
Filing Date
2023-11-24
Publication Date
2025-04-02
Estimated Expiration
2043-11-24

AI Technical Summary

Technical Problem

Ceramic materials used in electronic components, particularly ceramic capacitors, face challenges in achieving both high dielectric constant and low dielectric loss tangent simultaneously.

Method used

A dielectric ceramic with a composition of (Ti)x(Sn)1-x)O2 containing a rutile compound with 0.40≦x≦0.60 and Nb, where the Ti-rich and Sn-rich phases are controlled to form an island-like structure, achieving specific size and area ratios.

Benefits of technology

The dielectric ceramic achieves a low dielectric loss tangent of 0.035 or less and a high relative permittivity of 2400 or more, effectively addressing the limitations of existing ceramic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655447000002
    Figure 0007655447000002
  • Figure 0007655447000003
    Figure 0007655447000003
  • Figure 0007655447000004
    Figure 0007655447000004
Patent Text Reader

Abstract

Provided is a dielectric ceramic that can achieve both a low dielectric loss tangent and a high dielectric constant. The dielectric ceramic has a composition comprising, as a main component, a rutile-type compound represented by (TixSn1-x)O2 (0.40 ≤ x ≤ 0.60) and further comprising Nb. In a cross-sectional view, the dielectric ceramic includes regions comprising a Ti-rich phase in which A, defined by equation (1), is 0.55 or greater, and regions comprising a Sn-rich phase in which B, defined by equation (2), is 0.55 or greater, and the dielectric ceramic satisfies equations (3) to (5). (1): A = (Ti content (atom%)) / (total content (atom%) of Ti and Sn); (2): B = (Sn content (atom%)) / (total content (atom%) of Ti and Sn); (3): 0.005 mol% ≤ y ≤ 0.020 mol%; (4): 16 nm ≤ DTi ≤ 20 nm; (5): 15 nm ≤ DSn ≤ 19 nm, wherein y (mol%) is the content of Nb based on 100 mol% of the content of the rutile-type compound, DTi (nm) is the average dimension of the Ti-rich phase regions, and DSn (nm) is the average dimension of the Sn-rich phase regions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a dielectric ceramic and a ceramic capacitor using the same. [Background technology]

[0002] Metastable Ti 0.5 Sn 0.5 O 2 When ceramics are heat-treated and then rapidly cooled, they undergo spinodal decomposition, causing phase separation into a phase with a high Ti content (Ti-rich phase) and a phase with a high Sn content (Sn-rich phase), forming a striped structure with a width of 10 to 100 nm.

[0003] Ti 0.5 Sn 0.5 O 2 When Nb is added to ceramics as a donor, electrons are generated as carriers. When Nb-added ceramics are heat-treated to cause spinodal decomposition, the electrons are blocked by the barrier between the Ti-rich phase and the Sn-rich phase, and the ceramics has a high dielectric constant (for example, Non-Patent Document 1). [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] W. Chaisan et al., “The effects of the spinodal microstructure on the electrical properties of TiO2-SnO2 ceramics”, Journal of Solid State Chemistry 178 (2005) 613-620 Summary of the Invention [Problem to be solved by the invention]

[0005] Ceramic materials used in electronic components, especially ceramic capacitors, are required to have both a high relative dielectric constant and a low dielectric loss tangent. For example, ceramic materials with a dielectric loss tangent of 0.035 or less at 10 kHz and a relative dielectric constant of 2400 or more are required. However, the ceramic material disclosed in Non-Patent Document 1 fails to achieve both a low dielectric tangent and a high relative dielectric constant.

[0006] SUMMARY OF THE PRESENT EMBODIMENTS Accordingly, an object of the present invention is to provide a dielectric ceramic that can achieve both a low dielectric tangent and a high relative dielectric constant, and to provide a ceramic capacitor using the same. [Means for solving the problem]

[0007] According to one aspect of the present invention, The main component is (Ti x Sn 1-x )O 2 The composition includes a rutile compound represented by (0.40≦x≦0.60) and further includes Nb, In cross section, A region consisting of a Ti-rich phase in which A defined by the following formula (1) is 0.55 or more; A region consisting of an Sn-rich phase in which B defined by the following formula (2) is 0.55 or more, There is provided a dielectric ceramic that satisfies the following formulas (3) to (5). A = (Ti content (atom%)) / (Total content of Ti and Sn (atom%)) (1) B = (Sn content (atom%)) / (Total content of Ti and Sn (atom%)) (2) 0.005mol%≦y≦0.020mol% (3) 16nm≦D Ti <=20nm (4) 15nm≦D Sn <=19nm (5) Where: y (mol%) is the Nb content when the content of the rutile compound is 100 mol%, D Ti (nm) is the average size of the Ti-rich phase domains, D Sn (nm) is the average size of the Sn-rich phase domains.

[0008] According to another aspect of the present invention, A ceramic capacitor is provided that includes a ceramic body containing the dielectric ceramic of the present invention.

[0009] According to yet another aspect of the present invention, There is provided a multilayer ceramic capacitor including a ceramic body containing the dielectric ceramic of the present invention. Effect of the Invention

[0010] According to the present invention, it is possible to provide a dielectric ceramic that can achieve both a low dielectric tangent and a high relative dielectric constant, and a ceramic capacitor using the same. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic diagram for explaining an internal structure in a cross-sectional view of a dielectric ceramic according to a first embodiment of the present invention. [Diagram 2] 1 shows a STEM image of a cross section of a sample prepared in Example 1 of the present invention, and the results of examining the distribution of Ti, Nb, and Sn by EDX analysis from the TEM image. [Diagram 3] The distributions of Ti and Sn were determined by EDX analysis of the TEM image of the cross section of the sample prepared in Example 1 of the present invention, and the distributions of the Ti-rich phase and the Sn-rich phase were determined using the results shown below. [Figure 4] FIG. 1 is a schematic cross-sectional view of a multilayer ceramic capacitor according to a second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Ti disclosed in Non-Patent Document 1 0.5 Sn 0.5 O 2 It is difficult to achieve a low dielectric tangent in ceramics. The reason is unclear, but is presumed to be as follows.

[0013] Ti 0.5 Sn 0.5 O 2 Ceramics form a striped structure of Ti-rich and Sn-rich phases through spinodal decomposition. The striped structure extends in one direction within one crystal grain. It also extends in one direction within another crystal grain, but the extension direction does not necessarily match the extension direction within the adjacent crystal grain. Since it is difficult to control the direction of phase separation that occurs within a crystal grain, it is difficult to intentionally align the extension direction of the striped structure between adjacent crystal grains, or to intentionally make the extension directions different.

[0014] The crystal grains that make up ceramics have grain boundaries between adjacent crystal grains. The Ti-rich phase and the Sn-rich phase that make up the striped structure within a crystal grain each extend in a thin band-like state and terminate at the grain boundary with the adjacent crystal grain. When the end of each rich phase located at the grain boundary comes into contact with the end of the same type of rich phase in the adjacent crystal grain, a current path can be formed between the adjacent crystal grains.

[0015] For example, if an end of a Ti-rich phase in one crystal grain is in contact with an end of a Ti-rich phase in an adjacent crystal grain at a grain boundary, when a voltage is applied to the ceramic, electrons can flow from the Ti-rich phase in one crystal grain, through the grain boundary, to the Ti-rich phase in the other crystal grain. Similarly, if an end of a Sn-rich phase in one crystal grain is in contact with an end of a Sn-rich phase in an adjacent crystal grain at a grain boundary, when a voltage is applied to the ceramic, electrons can flow from the Sn-rich phase in one crystal grain, through the grain boundary, to the Sn-rich phase in the other crystal grain.

[0016] As described above, ceramics in which electrons are movable between adjacent crystal grains have a problem in that the dielectric tangent increases.

[0017] As a result of intensive research, the inventors have found that the Ti-rich phase and the Sn-rich phase generated by spinodal decomposition can be controlled to be island-like by controlling the heating conditions during ceramic firing. In dielectric ceramics having an island structure, current paths between adjacent crystal grains are unlikely to form, so that both a low dielectric tangent and a high relative dielectric constant can be achieved.

[0018] Hereinafter, a dielectric ceramic according to an embodiment of the present invention and a ceramic capacitor using the same will be described in detail.

[0019] [Embodiment 1] FIG. 1 is a schematic diagram for explaining the internal structure in a cross-sectional view of the dielectric ceramic according to the first embodiment. The dielectric ceramic 10 is mainly composed of (Ti x Sn 1-x )O 2 The dielectric ceramic 10 includes a rutile compound represented by (0.40≦x≦0.60) and further includes Nb. The dielectric ceramic 10 includes a large number of crystal grains 12 therein and grain boundaries 14 present between each of the crystal grains 12.

[0020] In a cross-sectional view, the dielectric ceramic 10 includes, within each crystal grain 12, a region (Ti-rich phase region 20) made of a Ti-rich phase in which A defined by formula (1) is 0.55 or more, and a region (Sn-rich phase region 30) made of a Sn-rich phase in which B defined by formula (2) is 0.55 or more. Within the crystal grain 12, the region that is neither the Ti-rich phase region 20 nor the Sn-rich phase region 30 is a ceramic phase in which A is less than 0.55 and B is less than 0.55 (i.e., the Ti content and Sn content are approximately the same). A = (Ti content (atom%)) / (Total content of Ti and Sn (atom%)) (1) B = (Sn content (atom%)) / (Total content of Ti and Sn (atom%)) (2)

[0021] The Ti content (atom %) and Sn content (atom %) at each measurement position can be measured by STEM-EDX (accelerating voltage: 200 kV, magnification: 60,000 times).

[0022] The dielectric ceramic 10 further satisfies the following formulas (3) to (5). 0.005mol%≦y≦0.020mol% (3) 16nm≦D Ti <=20nm (4) 15nm≦D Sn <=19nm (5) Where: y (mol%) is the Nb content when the content of the rutile compound is 100 mol%, D Ti (nm) is the average size of the Ti-rich phase domains, D Sn (nm) is the average size of the Sn-rich phase domains.

[0023] Formula (3) defines the content of Nb (donor) contained in the dielectric ceramic 10. By appropriately controlling the Nb content, it is possible to achieve both a low dielectric tangent and a high relative dielectric constant. The Nb content (mol %) can be measured by composition analysis using Inductively Coupled Plasma Atomic Emission Spectroscopy.

[0024] Formula (4) defines the average size of the Ti-rich phase region 20 , and formula (5) defines the average size of the Sn-rich phase region 30 . The average size is determined by the following procedure. The dielectric ceramics are observed by STEM-EDX (accelerating voltage: 200 kV, magnification: 60,000 times), and the Ti-rich phase region 20 and the Sn-rich phase region 30 are identified from the obtained content data of each element. Using image analysis software (e.g., image analysis software winROOF (Mitani Corporation)), 300 pieces of each rich phase region within the observation region are arbitrarily selected, and the maximum dimension of each is measured (Ferret II diameter (horizontal)). The average value of the obtained maximum dimension measurement data (300 pieces of data for each rich phase region) is calculated, and the "average dimension D of the Ti-rich phase region 20" is obtained. Ti (nm)” and “Average dimension D Sn When the number of rich phase regions included in one visual field observation is less than 300, the visual field observation is performed multiple times to select 300 rich phase regions and measure their dimensions.

[0025] In the dielectric ceramic 10 according to the first embodiment, the average dimension D Ti (nm) 16nm≦D Ti ≦20 nm, and the average dimension D of the Sn-rich phase region 30 Sn (nm) 15nm≦D Sn Each of the rich phase regions 20, 30 whose dimensions are controlled in this manner has an island-like structure having a certain size, and as a result, the dielectric ceramic 10 can achieve both a low dielectric tangent and a high relative dielectric constant. In addition, when the dielectric ceramic 10 includes a Ti-rich phase having a striped structure, the maximum dimension of the striped Ti-rich phase is much larger than the maximum dimension of the island-like Ti-rich phase. Therefore, the average dimension D Ti (nm) is estimated to be greater than 20 nm. Similarly, when the dielectric ceramic 10 includes a striped Sn-rich phase, the maximum dimension of the striped Sn-rich phase is much larger than the maximum dimension of the island-like Sn-rich phase. Therefore, the average dimension D Sn (nm) is estimated to be greater than 19 nm.

[0026] Preferably, the average dimension D of the Ti-rich phase region Ti More preferably, the average dimension D of the Ti-rich phase region is 16 nm or more and 18 nm or less. Ti is 16 nm or more and 17 nm or less. A dielectric ceramic 10 that can achieve both a lower dielectric tangent and a higher relative dielectric constant is obtained.

[0027] In a cross-sectional view, the area ratio α (%) of the Ti-rich phase region is preferably 5.50% or more and 7.10% or less when the area ratio of the dielectric ceramic excluding pores is taken as 100%. A dielectric ceramic 10 that can achieve both a lower dielectric tangent and a higher relative dielectric constant is obtained. More preferably, the area ratio α (%) is 5.50% or more and 6.80% or less, thereby making it possible to obtain a dielectric ceramic 10 that can achieve both a lower dielectric tangent and a higher relative dielectric constant.

[0028] The term "area ratio of the dielectric ceramic excluding pores is 100%" means that the content data of each element obtained by the above-mentioned STEM-EDX measurement is image-analyzed, and the area obtained by subtracting the area of ​​pores from the area of ​​the observation field is set to 100%. "Pores" refer to hollow portions present in the dielectric ceramic.

[0029] The method for identifying pores using image analysis is as follows. A Ti distribution image and a Sn distribution image taken from the same observation site are prepared. The Ti distribution image is analyzed to identify the maximum Ti detection intensity within the field of view, and all areas where the Ti detection intensity is 1 / 100th or less of that maximum detection intensity (low Ti concentration areas) are identified. Similarly, the Sn distribution image is analyzed to identify the maximum Sn detection intensity within the field of view, and all areas where the Sn detection intensity is 1 / 100th or less of that maximum detection intensity (low Sn concentration areas). The areas that are both low Ti concentration areas and low Sn concentration areas are then deemed to be "pores." In this specification, the "area ratio α (%) of Ti-rich phase region" refers to the area ratio calculated from the total area of ​​Ti-rich phase regions within the observation field where the dimension of the continuous Ti-rich phase (i.e., the maximum dimension of the Ti-rich phase region) is 14 nm or more.

[0030] The above various measurements are performed at the center of the dielectric ceramic.

[0031] [Manufacturing method of dielectric ceramics] The dielectric ceramic according to the first embodiment includes the following steps 1) to 5). 1) Mix raw materials containing Ti, Sn, and Nb in a specified ratio. 2) Calcining the mixed raw materials 3) Press the calcined powder into a mold 4) The molded body is fired at a firing temperature of more than 1505°C and less than 1520°C for a specified firing time. 5) After firing, cool quickly

[0032] It should be noted that this document differs from Non-Patent Document 1 in the following respects. In the first embodiment, the firing temperature in step 4) is high (in Non-Patent Document 1, the firing temperature is 1450°C). In the first embodiment, annealing is not performed after step 5) (in Non-Patent Document 1, annealing is performed at 1000°C for 1 to 48 hours after step 5))

[0033] The method for producing the dielectric ceramic according to the first embodiment will be described in detail below.

[0034] 1) Mix raw materials containing Ti, Sn, and Nb in a specified ratio. The raw materials serving as the Ti source, Sn source and Nb source are mixed so that the contents of Ti, Sn and Nb are in a desired ratio. As the raw materials, oxides of Ti, Sn and Nb can be used. The raw materials mixed in a predetermined ratio are mixed using a device such as a ball mill, high pressure dispersion, or jet mill. Either dry mixing or wet mixing can be used. In wet mixing, it is preferable to use an organic solvent such as ethanol or an inorganic solvent such as water as a solvent.

[0035] 2) Calcining the mixed raw materials The mixed raw materials are dried and granulated to produce raw material powder. The raw material powder is calcined at 900°C to 1400°C for 1 hour to 24 hours to obtain a solid solution. The calcination is performed in air or an oxygen atmosphere. An electric furnace or the like can be used for the calcination.

[0036] 3) Press the calcined powder into a mold The calcined powder is granulated and molded into a desired shape and size. Molding is performed by uniaxial pressing, CIP, WIP, etc. In addition, multiple molding methods may be applied sequentially. For example, CIP may be applied after molding by uniaxial pressing.

[0037] 4) The molded body is fired at a firing temperature of more than 1505°C and less than 1520°C for a specified firing time. The compact is sintered at a sintering temperature of more than 1505°C and less than 1520°C for 5 hours to 120 hours. By sintering in this temperature range, the Ti-rich phase region and the Sn-rich phase region can be made into an island shape. The sintering temperature is preferably 1510°C to 1515°C. The firing atmosphere is air, oxygen, etc. An electric furnace, millimeter wave furnace, infrared furnace, etc. may be used for firing. The heating rate is preferably 1° C. / min or more and 30° C. / min or less.

[0038] 5) After firing, cool quickly After the sintering is complete, the material is removed from the furnace and quenched in air or water, resulting in a structure in which the Ti-rich phase and the Sn-rich phase are separated into islands inside the crystal grains.

[0039] [Embodiment 2] In the second embodiment, a ceramic capacitor including a ceramic body containing the dielectric ceramic according to the first embodiment will be described. Ceramic capacitors include those that do not have internal electrodes inside the ceramic element (single-layer ceramic capacitors) and those that have a plurality of internal electrodes inside the ceramic element (multilayer ceramic capacitors). A single-layer ceramic capacitor corresponds to a multilayer ceramic capacitor without internal electrodes, and therefore the multilayer ceramic capacitor will be mainly described with reference to the drawings.

[0040] 4 is a schematic cross-sectional view of the multilayer ceramic capacitor 110. The multilayer ceramic capacitor 110 includes a ceramic body 400 and external electrodes 310, 320 provided on both ends of the ceramic body 400.

[0041] The ceramic body 400 is composed of multiple ceramic layers 405. Internal electrodes 410, 420 are provided inside the ceramic body 400. The internal electrodes 410, 420 and the ceramic layers 405 are alternately stacked to form the ceramic body 400. The internal electrodes 410, 420 are exposed from any of the end faces of the ceramic body 400 and are electrically connected to the external electrodes 310, 320.

[0042] The ceramic layers 405 of the ceramic body 400 used in the multilayer ceramic capacitor 110 are formed from the dielectric ceramic according to embodiment 1. Therefore, the ceramic layers 405 have a high relative dielectric constant and a small dielectric tangent, and thus the multilayer ceramic capacitor 110 can be obtained that has a large capacitance and generates little heat due to dielectric loss.

[0043] The materials of the external electrodes 310, 320 and internal electrodes 410, 420 used in the multilayer ceramic capacitor 110 and the method for manufacturing the multilayer ceramic capacitor 110 can be known materials for external electrodes and internal electrodes and known methods for manufacturing multilayer ceramic capacitors.

[0044] On the other hand, a single-layer ceramic capacitor uses a ceramic body that does not include internal electrodes, and external electrodes are provided on both ends of the ceramic body. The ceramic body used in the single-layer ceramic capacitor is made of the dielectric ceramic according to embodiment 1. Therefore, it is possible to obtain a single-layer ceramic capacitor that has a large electric capacity and generates little heat due to dielectric loss. EXAMPLES

[0045] A) Preparation of sintered dielectric samples As raw material, TiO 2 , SnO 2 and Nb 2 O 5 The raw materials were weighed so that the contents of Ti, Sn, and Nb were in the relationship of the contents of each element shown in Table 1, and an organic solvent such as ethanol was added and wet-mixed for a specified time using a ball mill. The dried and granulated powder was then calcined in air at 1100°C for 6 hours to obtain a solid solution. This powder was granulated and pressed into a 10 mm diameter molder at 20 MPa for 1 minute using uniaxial pressure, and further subjected to CIP treatment at 125 MPa for 1 minute to obtain a green body. This molded body was sintered in air for 24 hours at the sintering temperature shown in Table 1 to obtain a dense dielectric sintered body (hereinafter sometimes referred to as "sintered body"). The temperature increase rate during sintering was 5°C / min, and rapid cooling was performed in air when the temperature was decreased.

[0046] B) Characterization (1) Measurement of the average dimensions of the Ti-rich and Sn-rich phase regions of sintered samples The sintered sample was embedded in the resin with all of its outer surfaces covered with epoxy resin. After the epoxy resin was cured, the sample was mirror-polished together with the epoxy resin. Then, it was cut into pieces with a thickness of 80-1200 nm using FIB and Pt sputtered. The Ti, Sn, and Nb (atom%) in the sintered sample were measured using STEM-EDX. The STEM was observed at an accelerating voltage of 200 kV and a magnification of 60,000 times (Figure 2). The distribution data of each element obtained from STEM-EDX (Figure 2) was image-processed and output as a 256 x 256 cell CSV file. The content (atom%) of each element at the measurement point corresponding to the position of the cell was entered in each cell. Using the Ti distribution data (csv file of Ti content (atom%)) and the Sn distribution data (csv file of Sn content (atom%)), the value of A at the measurement position corresponding to each cell was calculated using the following formula (1), and the value of B at the measurement position corresponding to each cell was calculated using the following formula (2). A = (Ti content (atom%)) / (Total content of Ti and Sn (atom%)) (1) B = (Sn content (atom%)) / (Total content of Ti and Sn (atom%)) (2)

[0047] Using the spreadsheet software Excel (Microsoft Corporation), mapping data (Ti mapping data) in which the calculation result (A value) of formula (1) is entered in a range of 256 cells x 256 cells, and mapping data (Sn mapping data) in which the calculation result (B value) of formula (2) is entered in a range of 256 cells x 256 cells were created.

[0048] For the Ti mapping data, Excel borders were hidden and the text color in each cell was changed to white. Furthermore, the Excel function "Conditional Formatting" was applied to make the background and text colors of cells with an A value of 0.55 or greater the same color (e.g. red). After processing the data in this way, the range of 256 cells x 256 cells in which values ​​were entered was saved as image data (jpg file) (Figure 3).

[0049] Similarly, for the Sn mapping data, the Excel borders were hidden and the text color in each cell was changed to white. Furthermore, the Excel function "Conditional Formatting" was applied to make the background and text colors of cells with a B value of 0.55 or greater the same color (e.g. red). After processing the data in this way, the range of 256 cells x 256 cells in which values ​​were entered was saved as image data (jpg file) (Figure 3).

[0050] When the value of A is 0.55 or more (A≧0.55), the measurement position is determined to be a "Ti-rich phase," and when the value of B is 0.55 or more (B≧0.55), the measurement position is determined to be made up of a "Sn-rich phase." In other words, in Ti image data created by processing Ti mapping data, a colored portion (e.g., a red portion) indicates that the portion is a Ti-rich phase. Similarly, in Sn image data created by processing Sn mapping data, a colored portion (e.g., a red portion) indicates that the portion is a Sn-rich phase.

[0051] The Ti image data was read into the image analysis software winROOF (Mitani Shoji), the maximum Ti detection intensity within the field of view was identified, and all areas where the Ti detection intensity was 1 / 100th or less of that maximum detection intensity (low Ti concentration areas) were identified. The Sn image data was analyzed in the same way, and all areas where the Sn detection intensity was 1 / 100th or less of the maximum Sn detection intensity (low Sn concentration areas) were identified. Areas that were both low Ti concentration areas and low Sn concentration areas were identified as "pores." The Ti image data was analyzed again, and the area excluding the pores was designated as the "area to be analyzed" and a file (roi file) was created. The Sn image data was also analyzed again in the same way, and a roi file was created.

[0052] In the roi file of the Ti image, the clusters in the red areas were regarded as Ti-rich phase regions. The Ti-rich phase regions were island-like. 300 Ti-rich phase regions were randomly selected from within the observation area, and the maximum dimension of each region (Ferret II diameter (horizontal)) was measured. The average of the obtained maximum dimension measurement data (300 data) was called the "average dimension D of the Ti-rich phase region." Ti (nm)".

[0053] Similarly, for the Sn image roi file, the clusters in the red areas were considered to be Sn-rich phase regions. The Sn-rich phase regions were also island-like. 300 Sn-rich phase regions were randomly selected from within the observation area, and the maximum dimension of each region (Ferret II diameter (horizontal)) was measured. The average of the maximum dimension measurement data (300 data) was defined as the "average dimension D of the Sn-rich phase region." Sn (nm)".

[0054] In addition, the total area of ​​the Ti-rich phase regions (the sum of the areas of all Ti-rich phase regions included in the observation range) was calculated in the roi file of the Ti image, and the area ratio of the total area of ​​the Ti-rich phase regions was calculated when the area of ​​the "region to be analyzed" was set to 100%. The measurement targets were Ti-rich phase regions with a maximum dimension of 14 nm or more within the observation field of view. Ten roi files of Ti images created from STEM-EDX measurement data measured at different positions were prepared, and the area ratio of the total area of ​​the Ti-rich phase region was calculated for each file, and the average value was taken as the "area ratio α (%) of the Ti-rich phase region."

[0055] (2) Composition analysis of dielectric sintered bodies The composition of the sintered samples was analyzed using inductively coupled plasma atomic emission spectroscopy. Standard solutions were used to quantify each element, and a calibration curve was created within the range of known concentrations to determine the relative sample concentrations.

[0056] (3) Measurement of electrical characteristics After mirror polishing on both sides of the sintered compact sample, electrodes were formed by sputtering, and the capacitance and dielectric tangent (dielectric loss) of the sintered compact sample were measured. The measurement method was in accordance with JIS C 5101-1:2019(4.7.1) and JIS C 5101-1:2019(4.8.1). However, the measurement frequency was 10kHz. From the measurement results of the electrostatic capacitance, the relative dielectric constant of the sintered body sample was calculated.

[0057] The evaluation criteria for the electrical properties were as follows: In measurements at 10 kHz, a dielectric loss tangent of 0.035 or less and a relative dielectric constant of 2400 or more was rated as "Pass (D)". Furthermore, a dielectric loss tangent of 0.030 or less and a relative dielectric constant of 2500 or more was rated as "C", a dielectric loss tangent of 0.025 or less and a relative dielectric constant of 2550 or more was rated as "B", and a dielectric loss tangent of 0.020 or less and a relative dielectric constant of 2600 or more was rated as "A". If at least one of the dielectric loss tangent exceeding 0.035 or the relative dielectric constant being less than 2400 was not satisfied, it was rated as "Fail (F)".

[0058] The measurement results are shown in Table 1.

[0059] [Table 1]

[0060] Examples that satisfy all the requirements stipulated in the first embodiment have good relative dielectric constants and dielectric loss tangents, and were rated A to D. Examples in which the area fraction α (%) of the Ti-rich phase region is 5.50% or more and 7.10% or less have better relative dielectric constants and dielectric loss tangents, and were rated C or higher. Furthermore, examples in which the area fraction α (%) is 5.50% or more and 6.80% or less and the average dimension D of the Ti-rich phase region is 1.0 or more and 1.0 or less, respectively, have better relative dielectric constants and dielectric loss tangents, and were rated C or higher. Ti In the examples where the average dimension D is 16 nm or more and 18 nm or less, the relative dielectric constant and the dielectric loss tangent are particularly good, and the examples were rated B or higher. Ti The examples having a dielectric constant of 16 nm or more and 17 nm or less had the best dielectric constant and dielectric tangent, and were rated A.

[0061] The comparative examples that did not satisfy one or more of the requirements defined in the first embodiment were rated as F because one or more of the relative dielectric constant and the dielectric loss tangent were lower than the pass line.

[0062] The disclosure of this specification may include the following aspects. <1> The main component is (Ti x Sn 1-x )O 2 The composition includes a rutile compound represented by (0.40≦x≦0.60) and further includes Nb, In cross section, A region consisting of a Ti-rich phase in which A defined by the following formula (1) is 0.55 or more; A region consisting of an Sn-rich phase in which B defined by the following formula (2) is 0.55 or more, A dielectric ceramic satisfying the following formulas (3) to (5): A = (Ti content (atom%)) / (Total content of Ti and Sn (atom%)) (1) B = (Sn content (atom%)) / (Total content of Ti and Sn (atom%)) (2) 0.005mol%≦y≦0.020mol% (3) 16nm≦D Ti <=20nm (4) 15nm≦D Sn <=19nm (5) Where: y (mol%) is the Nb content when the content of the rutile compound is 100 mol%, D Ti (nm) is the average size of the Ti-rich phase domains, D Sn (nm) is the average size of the Sn-rich phase domains.

[0063] <2> In a cross-sectional view, the area ratio α (%) of the Ti-rich phase region is 5.50% or more and 7.10% or less when the area ratio of the dielectric ceramic excluding pores is 100%. <1> The dielectric ceramic according to claim 1.

[0064] <3> The area ratio α (%) is 5.50% or more and 6.80% or less. <2> The dielectric ceramic according to claim 1.

[0065] <4> The average dimension D of the Ti-rich phase region Ti is 16 nm or more and 18 nm or less, <1> ~ <3> 13. The dielectric ceramic according to claim 12,

[0066] <5> The average dimension D of the Ti-rich phase region Ti is 16 nm or more and 17 nm or less, <1> ~ <4> 13. The dielectric ceramic according to claim 12,

[0067] <6> <1> ~ <5> 2. A ceramic capacitor comprising a ceramic body containing the dielectric ceramic according to claim 1.

[0068] <7> <1> ~ <5> 13. A multilayer ceramic capacitor comprising a ceramic body containing the dielectric ceramic according to any one of claims 1 to 12.

[0069] This application claims priority based on Japanese Patent Application No. 2023-030206, filed in Japan on February 28, 2023, the entire contents of which are incorporated herein by reference. [Explanation of symbols]

[0070] 10. Dielectric Ceramics 12 Grains 14 Grain boundaries 20 Ti-rich phase region 30 Sn-rich phase region 110 Multilayer ceramic capacitor 310, 320 external electrode 400 Ceramic body 405 Ceramic Layer 410, 402 Internal electrode

Claims

1. The main component is (Ti x Sn 1-x ) O 2 (0.40≦x≦0.60) and further containing Nb; In cross section, A region consisting of a Ti-rich phase in which A defined by the following formula (1) is 0.55 or more; A region consisting of a Sn-rich phase in which B defined by the following formula (2) is 0.55 or more, A dielectric ceramic that satisfies the following formulas (3) to (5). A = (Ti content (atom%)) / (Ti and Sn total content (atom%)) (1) B = (Sn content (atom%)) / (Total content of Ti and Sn (atom%)) (2) 0.005mol%≦y≦0.020mol% (3) 16nm≦D Ti ≦20nm (4) 15nm≦D Sn ≦19nm (5) Where: y (mol%) is the Nb content when the content of the rutile compound is 100 mol%, D Ti (nm) is the average size of the Ti-rich phase domains; D Sn (nm) is the average size of the Sn-rich phase domains.

2. 2. The dielectric ceramic according to claim 1, wherein, in a cross-sectional view, an area ratio α (%) of the Ti-rich phase region is 5.50% or more and 7.10% or less when an area ratio of the dielectric ceramic excluding pores is 100%.

3. The dielectric ceramic according to claim 2, wherein the area ratio α (%) is 5.50% or more and 6.80% or less.

4. The average dimension D of the Ti-rich phase region Ti The dielectric ceramic according to claim 1, wherein the average particle diameter is 16 nm or more and 18 nm or less.

5. The average dimension D of the Ti-rich phase region Ti The dielectric ceramic according to claim 1, wherein the average particle diameter is 16 nm or more and 17 nm or less.

6. A ceramic capacitor comprising a ceramic body containing the dielectric ceramic according to any one of claims 1 to 5.

7. A multilayer ceramic capacitor comprising a ceramic body containing the dielectric ceramic according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Microwave dielectric ceramic and preparation method thereof

    CN105777116A

  • Microwave dielectric ceramic and preparation method thereof

    CN105884351A

  • Dielectric porcelain

    JP2006008449A

  • Dielectric porcelain and method for producing the same

    JP2016145119A

  • Dielectric composition and electronic component

    JP2018140891A